Selection of the optimal number of shifts in fuzzy environment: Manufacturing company's facility application - Sanjoy Kumar Paul; Abdullahil Azeem (Journal of Industrial Engineering and Management (JIEM), 2010)
This paper addresses the selection of optimal shift numbers considering inventory information, customer requirements and machine reliability using fuzzy logic. Number of shift is one of the most important criteria for the production planners to minimize the production costs and is essential for appropriate production planning. The main task involves optimizing the shift periods considering constraints of raw material, due date, demand, finished goods inventory and machine breakdown. A model is developed for any kind of manufacturing company where shift periods affect company's profit and cost. Fuzzy control is used to optimize the number of shifts under the constraints of raw material, due date, demand, finished goods inventory and machine breakdown. MATLAB Fuzzy Logic Tool Box is used to develop the model.
Keywords: 650; optimal shift period; fuzzy logic; fuzzy set; production planning